Diagnosing autistic disorders — case report - Komorowska-Szczepańska, Wanda; Nowicka-Sauer, Katarzyna; Hansdorfer-Korzon, Rita; Pietrzykowska, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. In recent years the diagnosis of autism spectrum disorders (ASD) seems to be more prevalent. This fact may be caused not only by increased concern and higher awareness of the disease but also by more efficient diagnostic methods. Aim. The aim of this paper was to present the medical history and symptoms observed in a boy from his birth till establishing diagnosis of autism and to discuss the problem of ASD. Material and methods. We describe the case of the boy diagnosed with autism at 16 months of age. Results and conclusion. The first atypical symptoms in the boy’s behaviour were observed at 10 months of age. Previously no psychomotor disorders were noticed. During medical examination in physician’s office, the child was screaming and crying. The boy was not making eye contact. Most of the time the child was focused only on a toy held in his hand. Scream as a reaction to loud sounds was observed. The boy’s mother noticed that he was upset when changes in daily schedule were made. Speech development was not observed. Motor development was harmonious. At the age of 12 months the boy was referred to a specialist. When he was 16 months of age, autistic disorder was diagnosed. Both family and multidisciplinary team are involved in therapy. The parents’ awareness and growing knowledge of health professionals, especially paediatrician, family physician and paediatric nurse, seem to be essential for early diagnosis of autism spectrum disorders. Nursing Topics 2014; 22 (1): 119–122